The relative importance of strong column-weak beam design concept in the single-story RC frames. (15th April 2019) - Vafaei, Mohammadreza; Baniahmadi, Mahmoud; Alih, Sophia C.
Highlights: Two full-scale RC frames namely SBF and OBF were subjected to the reversed cyclic loading. The relative importance of strong column-weak beam (SCWB) design concept was investigated. Both frames exhibited similar ultimate load and displacement ductility ratio. SBF showed an improved displacement at ultimate load and the effective yield strength. SBF exhibited a slower stiffness degradation rate for small to medium drift ratios. Abstract: Although seismic codes have determined all the required details for achieving different ductility classes, the relative importance of such details has not been well understood. This study investigated the relative importance of Strong Column-Weak Beam (SCWB) design concept in comparison to other code-prescribed details for a reinforced concrete Special Moment Frame (SMF). Two full-scale Reinforced Concrete (RC) frames were constructed with similar reinforcement ratios, geometry, and material properties. The first frame (i.e. OBF) only complied with the code-specified requirement for the strong column-weak beam design concept. However, the second frame (i.e. SBF) satisfied all other code-prescribed requirements for an SMF. Frames were subjected to a similar reversed cyclic loading and their response was compared. Results indicated that compared with SBF, OBF had an almost similar ultimate load, effective stiffness, displacement at effective yield strength, and displacement ductility ratio. Conforming to all code-prescribed details improved the displacement at ultimate load and the effective yield strength by an average of 25%. Moreover, although SBF exhibited a slower stiffness degradation rate for small to medium drift ratios, both frames achieved a similar lateral stiffness at large drift ratios.